GIS Scoring and Overlay Methods for Mapping Landslide Vulnerability in Lebak Regency, Banten - Sandri Erfani; Muhammad Naimullah; Denta Winardi (Lambung Mangkurat University Press, 2023)
Landslide hazard mapping using a geographic information system (GIS) is essential because it helps reduce disaster risks and protects communities from their impacts. In landslide hazard mapping, scoring and weighting methods and overlay analysis help determine the level of landslide vulnerability. The research data uses several parameters, including soil type, geology, rainfall, land cover, and slope. The slope was determined based on the Digital Elevation Model Shuttle Radar Topography Mission (DEM SRTM) data. The tools used are ArcGIS v10.8 software and Microsoft Office 2019. Lebak Regency has quite a lot of rainfall, especially during the rainy season, with moderate to dry intensity ranging from 1,501-2,000 mm/year and 2,001-2,500 mm/year. Stones that are easily worn and corroded are more vulnerable. Steep slopes can increase the risk of landslides, especially in areas with slippery soil types. Land cover converted to plantations or settlements tends to be more vulnerable than untouched land. Lebak Regency consists of 3 landslides: low, medium, and high. The area of low risk is 3,854.57 ha, the medium risk area is 160,884.09 ha, and the high-risk area is 164993.60 ha. Landslide-prone areas with a predominance of landslide vulnerability are shown in low level found in Wanasalam District, with an area of 2,800.91 ha or 0.08%; moderate level is found in Cileles District, with an area of 14,001.21 ha or 0.042%, and the high level is found in Cibeber District with an area of 32,501.61 ha or 0.098%.